INFLUENCE FACTORS ON THE LABORATORY TESTING OF GEOTEXTILES UNDER CONTROLLED ENVIRONMENT - D. T. Bergado; S. Youwai; J. Maneecharoen (International Association of Lowland Technology, 2002)
In order to investigate the influence factors affecting index and engineering properties of geotextiles under controlled environtments, different tests were conducted using both heat-bonded nonwoven and needle-punched nonwoven geotextiles, namely: apparent opening size (AOS), wide-width tensile strength, premittivity, transmissivity, and puncture resistance. The effect of humidity on the pore size og the samples was also investigated. To sheck whether the clamping system has an effect on the strength of geotextiles, over 24o tests were conduted. The presence of air bubbles in water and its effect on the permittivity and transmissivity of geotextiles were also verified. Also investigated were the effects of higher strain rate and displacement rate on the tensile strength and puncture resistancem respectively. The results indicate that decreasing humidity slightly increased the AOS; higher strain rate and the use of hydraulic clamp increased the wide-width tensile strength; using de-aired water largely improved the permittivity and transmissivity; and increasing the strain rate decreased the puncture resistance. The effects of humidity and oxygen content were more pronounced and obvious in the case of needle-punched geotextile compared to heat-bounded nonwoven geotextile.